Socio economic characteristics of milk producers of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
A survey was conducted to know the socio economic characteristics of milk producers of irrigated and  rainfed areas of Visakhapatnam district of Andhra Pradesh. The data pertaining to the socioeconomic  characteristics  of  200  dairy  farmers  from  50  different  villages  were  collected  by  using  a  pretested  questionnaire through personal interview and the data were analysed. The study revealed that an overall  12.50, 74.50 and 13.00 per cent of respondents were found to be young age, middle age and old age,  respectively, in the study area. An overall 17.5, 1.5, 29.5 and 51.50 per cent belonged to scheduled caste,  scheduled tribe, backward caste and other caste, respectively in the study area. Most of the milk producers  were literate ranging from primary to graduation level of education, out of which majority of them had high  school education in irrigated and rainfed areas. Majority of milk producers in Visakhapatnam district had  agriculture as main occupation while dairying as subsidiary occupation. Most of the milk producers were  of small farmers followed by landless, marginal, medium and large farmers with small family size. Majority  of milk producers had extension contact with veterinarians followed by para veterinarians and had mass  media exposure with television and radio to get information about dairying.
Keywords: Socio economic; Milk producers; Irrigated; Rainfed